Implementation of The Cooperative Learning Method of the Numbered Heads Together (NHT) Type to Improve PAI Learning Motivation in Fifth-Grade Students of SDN Telukjambe I - Naila Waridatus Sa'adah; Najwa Aulia; Fatihul Noer Ihsan; M Makbul (CV. Kayaswara, 2026)
Purpose of the Study: This study aims to improve the motivation to learn of fifth-grade students in Islamic Religious Education (PAI) at SDN Telukjambe I by implementing the Numbered Heads Together (NHT) cooperative learning model. The research addresses the problem of low student motivation in PAI learning by examining how a structured, team-based numbering strategy can foster greater activity, responsibility, cooperation, confidence, and participation in the subject matter. Methodology: This research employs Classroom Action Research (CAR), involving researchers and teachers, conducted over two cycles, with two meetings in each cycle. The participants were 36 fifth-grade students at SDN Telukjambe I. Data were collected using observation sheets, learning motivation questionnaires, and cognitive-domain achievement tests. The data were analyzed using descriptive statistics, in which the mean and percentage of students' learning motivation scores were calculated to determine the category of motivation achieved. Main Findings: The implementation of the NHT model led to a measurable improvement in students' learning motivation, rising from an initial benchmark score of 79.4% (high) to 84.4% (high) in Cycle I and reaching 91.4% (very high) in Cycle II. These findings demonstrate that the collaborative, structured pattern of the NHT model effectively stimulates motivation and encourages students to be more active, responsible, cooperative, confident, and participatory in the learning process. Novelty/Originality of this Study: This study provides practical evidence on the application of the Numbered Heads Together (NHT) cooperative learning model in the specific context of Islamic Religious Education (PAI) at the elementary school level. It offers a replicable, classroom-tested strategy for enhancing students' motivation to learn in religious subjects, providing a foundation for educators seeking active-learning alternatives to conventional, lecture-based PAI instruction.